PERLINDUNGAN HUKUM DAN MEKANISME HAK MENUNTUT GANTI RUGI BAGI KORBAN TINDAK PIDANA AKIBAT KESALAHAN PENANGKAPAN DAN PENAHANAN - Mhd. Ansori Lubis; Fitriani Fitriani; Nata Pardamean Panjaitan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
A suspect, defendant or convict has the right to receive protection if he becomes a victim in a criminal justice process, that is, if an arrest and detention is made that is not in accordance with legal procedures. This research method is juridical normative. The formulation of the problems in this research are: How do the arrangements for providing compensation for victims of criminal acts due to wrongful arrest and detention, what reasons cause the victim of a crime to sue for compensation and how legal protection and the mechanism for prosecuting compensation for damages. compensation is contained in Article 9 of Law Number 48 of 2009 concerning Judicial Powers, Article 95, Article 96 of the Criminal Procedure Code, for compensation for victims regulated in Article 98 to Article 102. The reasons that cause victims to demand compensation are: a). Unauthorized arrest, b). Illegal detention, c). Prosecuted and tried without being based on law, d). Losses due to actions without reason under the law, e) Termination of investigation and termination of prosecution, f). Compensation after review. The form of legal protection for victims is contained in Government Regulation Number 92 of 2015 concerning the Second Amendment to Government Regulation Number 27 of 1983 concerning the Implementation of the Criminal Procedure Code. the mechanism for filing compensation is stated in Article 79, Article 95 paragraph (2), Article 80 of the Criminal Procedure Code.